Kurikulum Pak yang Holistik: Mengintegrasikan Aspek Afektif dan Psikomotorik dalam Pembelajaran Agama Kristen - Natalia Natalia (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the development of a holistic Christian Religious Education (PAK) curriculum by integrating affective and psychomotor domains into the learning process. The topic is significant because the current PAK curriculum predominantly emphasizes cognitive and doctrinal aspects, resulting in Christian values being taught theoretically without practical application in students’ daily lives. A qualitative descriptive approach was employed to investigate and develop a balanced curriculum model that integrates theory, spiritual internalization, and practical skills. The findings reveal that a holistic curriculum enhances faith internalization and character formation in students, making the learning process more relevant and transformative. Implementation of this curriculum model promotes Christian education as an integrative process encompassing knowledge, attitudes, and practical competencies in real-life contexts.